Impact of intubated vs. non-intubated anesthesia on postoperative diaphragmatic function: Results from a prospective observational study - Steinberg, Irene; Bisciaio, Agnese; Rosboch, Giulio Luca; Ceraolo, Edoardo; Guerrera, Francesco; Ruffini, Enrico; Brazzi, Luca (Frontiers in Physiology, 2022)
Background: An altered diaphragmatic function was associated with the development of postoperative pulmonary complications following thoracic surgery. Methods: To evaluate the impact of different anesthetic techniques on postoperative diaphragmatic dysfunction, patients undergoing video-assisted thoracoscopic surgery (VATS) lung biopsy for interstitial lung disease were enrolled in a monocentric observational prospective study. Patients received intubated or non-intubated anesthesia according to risk assessment and preferences following multidisciplinary discussion. Ultrasound measured diaphragmatic excursion (DIA) and Thickening Fraction (TF) were recorded together with arterial blood gases and pulmonary function tests (PFT) immediately before and 12 hours after surgery. Pain control and postoperative nausea and vomiting (PONV) were also evaluated. Results: From February 2019 to September 2020, 41 consecutive patients were enrolled. Five were lost due to difficulties in collecting postoperative data. Of the remaining 36 patients, 25 underwent surgery with a non-intubated anesthesia approach whereas 11 underwent intubated general anesthesia. The two groups had similar baseline characteristics. On the operated side, DIA and TF were more reduced from baseline in the intubated group than in the non-intubated group (54% vs 82% for DIA and 36% vs 97% for TF of the preoperative function; p=0.001 for both). The same was observed on the non-operated side (58% vs 82% and 62% vs 94%; p=0.005 and p=0.045 respectively for DIA and TF). No differences were observed between groups in terms of pain control, PONV, gas exchange, and PFT. Conclusions: This study suggests that maintenance of spontaneous breathing during VATS lung biopsy is associated with better diaphragmatic postoperative function.